IMF Committee on Balance of Payments Statistics : Annual Report 2010. (Balance of Payments Statistics; Balance of Payments Statistics ;, 2011)
The Annual Report of the IMF Committee on Balance of Payments Statistics (Committee) for 2010 provides an overview of recent trends in global balance of payments and international investment position (IIP) statistics, including the latest developments in data from the Coordinated Portfolio Investment Survey (CPIS). Furthermore, the report summarizes the Committee's work program during 2010, and reviews the issues the Committee plans to address in the coming year.